Food safety : contaminants and toxins (CABI, 2003)
This textbook covers the recent developments in the chemistry, biochemistry and physiological effects of contaminants that might have an impact on human health and welfare. It also discusses risk management and regulatory issues. It contains 19 chapters that are divided into 4 sections. The first part includes chapters on plant and microbial toxins that may contribute to common cases of food allergies, intolerance and poisoning. The second part deals with contaminants arising from anthropogenic activities and environmental pollution, such as polychlorinated biphenyls, dioxins, polycyclic aromatic hydrocarbons, heavy metals, nitrates, nitrites, nitroso compounds, food additives, and drugs. The third part comprises case studies on current topics of particular concern in food safety. Specific emphasis is placed on the nature of compounds, distribution of residues in common foods, uptake, toxicology and regulatory issues. In the fourth part, a concluding chapter contains a synthesis of the worldwide and continuing concerns over food safety using information from all chapters in the book. Emerging issues and legislation are also addressed, and the chapter ends with a review of research priorities and action points. This book will be of considerable interest to students and researchers in food science, dietetics, medical and veterinary sciences and agriculture.